2020
DOI: 10.3390/ijerph17062027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Disaster Medicine Preparedness among Healthcare Profession Students: A Cross-Sectional Study in Pakistan

Abstract: Background: Disasters are devastating incidents, especially when occurring suddenly and causing damage, great loss of life, or suffering. Disasters can affect health and the social and economic development of a nation. The article analyzes the knowledge (K), attitude (A), and readiness to practice (rP) of healthcare professional students in universities in Pakistan. Methods: We carried out a cross-sectional study using a pretested and validated self-administered disaster medicine and preparedness questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…A self-reported rapid online-based survey was selected because of ongoing lockdown in the country and it was easily reachable to the university students (Tanner & Doberstein, 2015). Many relevant research have already been employed self-reported survey successfully (Basolo et al, 2009;Bourque et al, 2012;Gillani et al, 2020;Nguyen et al, 2006). Concentrating on the country's COVID-19 worst affected capital city, area was divided into two categories; Dhaka and outside Dhaka.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A self-reported rapid online-based survey was selected because of ongoing lockdown in the country and it was easily reachable to the university students (Tanner & Doberstein, 2015). Many relevant research have already been employed self-reported survey successfully (Basolo et al, 2009;Bourque et al, 2012;Gillani et al, 2020;Nguyen et al, 2006). Concentrating on the country's COVID-19 worst affected capital city, area was divided into two categories; Dhaka and outside Dhaka.…”
Section: Methodsmentioning
confidence: 99%
“…This study has attempted to measure the knowledge level, attitude, and practices among university students of Bangladesh. Prior to this study, knowledge, attitude, and practices have successfully been used in many research to estimate the preparedness and response level of students (Basir et al, 2020;Chen et al, 2015;Gillani et al, 2020;Hayat et al, 2020;Zhong et al, 2020). Cross sectional study was conducted to identify the vulnerable group toward COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study followed self-reported rapid online-based survey method due to the ongoing COVID-19 pandemic in Bangladesh. Many relevant researches have already been applied to self-reported surveys successfully (Basolo et al, 2009;Bourque et al, 2012;Gillani et al, 2020;Nguyen et al, 2006;Rahman et al, 2020;Tan et al, 2017;Wang et al, 2020). This study considered the worst COVID-19 affected capital city Dhaka as the county's epicenter for the pandemic.…”
Section: Study Design and Ethical Issuesmentioning
confidence: 99%
“…At the same time, many studies believe that the residents’ preparedness for avoiding disasters is simply material preparation, which is measured from the perspective of residents’ material preparation. Among them, the most common way to measure disaster preparedness is to ask residents whether they have prepared emergency disaster kits (flashlights, radios, clean water) (e.g., [ 35 , 36 , 45 , 46 ]), buy insurance (e.g., [ 24 , 25 ]), if they had an escape plan (e.g., [ 39 , 40 , 41 , 42 , 47 , 48 ]) and reinforce houses (e.g., [ 38 , 49 ]). In addition, some scholars have noted that in addition to material preparation, residents’ disaster preparedness, conscious disaster risk management behavior is also an effective means to deal with disaster impact (e.g., [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis of introduction, referring to the disaster risk management literature, this study measures disaster-preparedness behavior in three dimensions: (1) emergency-disaster preparedness, (2) knowledge and skills preparedness and (3) physical disaster-prevention preparedness ( Table 1 ). Among them, the selection of emergency-disaster preparedness dimension measurement indicators is based on references [ 35 , 36 , 45 , 46 ], the selection of knowledge and skills preparedness dimension measurement indicators is based on references [ 24 , 25 , 38 , 49 ] and the selection of knowledge and skills preparedness dimension measurement indicators is based on references [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%